Smoking, alcohol, and dietary choices: evidence from the Portuguese National Health Survey - Santos Ana; Lunet Nuno; Padrão Patrícia; Barros Henrique (BMC, 2007)
Abstract Background Unhealthy lifestyle choices tend to cluster, but controversy remains regarding relationships between smoking and dietary habits. The aim of this study was to compare dietary intake and alcohol consumption, according to smoking status, in the Portuguese population. Methods The study sample included all participants in the third Portuguese National Health Survey who were older than 19 years (20,302 women and 17,923 men). Participants were selected from households in the five regions of Portugal (NUTS II classification), using a multi-stage random probability design. Trained interviewers conducted face-to-face interviews in each household and obtained information on social and demographic characteristics, lifestyle and health, smoking, and intakes of selected food and beverages. Age-adjusted and education-adjusted binomial and multinomial logistic regression models were fitted separately for males and females, to estimate the magnitude of the association between smoking and the consumption of various food and beverage groups. Results When heavy smokers were compared with non-smokers, the odds ratio (OR) favouring soup consumption was 0.60 (95% Confidence Interval [95%CI]: 0.54-0.68) in males and 0.46 (95% CI: 0.33-0.65) in females. Similar ORs were observed for vegetables (males: OR = 0.56, 95%CI: 0.49-0.64; females: OR = 0.47, 95%CI: 0.32-0.69) and fruit (males: OR = 0.36, 95%CI: 0.31-0.41; females: OR = 0.29, 95%CI: 0.19-0.44). Overall, these food items were consumed at significantly lower levels as cigarette consumption increased. Heavy male smokers, compared to non-smokers, presented lower odds favouring milk consumption (OR = 0.89; 95%CI: 0.67-0.89). When heavy smokers were compared with non-smokers, the ORs favouring wine drinking, among heavy drinkers, were 1.47 (95%CI: 1.27-1.70) in men and 3.97 (95%CI: 2.07-7.61) in women. Similar ORs were observed for beer (males: OR = 3.30; 95%CI: 2.87-3.78; females: OR = 23.1; 95%CI: 12.2-43.6), Port wine (males: OR = 2.21 95%CI: 1.65-2.98; females: OR = 2.85; 95%CI: 0.68-12.1), brandy (males: OR = 3.67 95%CI: 2.98-4.52; females: OR = 13.2; 95%CI: 3.72-46.6) and whisky (males: OR = 3.31; 95%CI: 2.71-4.03; females: OR = 41.4; 95%CI: 18.5-92.5). Conclusion This study showed that smokers have a higher intake of alcoholic beverages and a lower consumption of food items rich in fibre, antioxidants, or phytochemicals, which are suspected to have beneficial roles in the prevention of multiple chronic diseases.